2021
DOI: 10.1007/s00420-021-01760-5
|View full text |Cite
|
Sign up to set email alerts
|

Overtime working patterns and adverse events in work-related suicide cases: hierarchical cluster analysis of national compensation data in Japan (fiscal year 2015–2016)

Abstract: Background Although various work-related adverse events affect workers’ mental health, the association between long working hours and mental disorders remains unclear. We investigated the characteristics of overtime work and work-related adverse events among all cases of compensated work-related suicide in Japan to empirically reveal the context of the serious consequences. Methods We analysed all 167 cases of mental disorders resulting in suicide that wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…The JDC model shows a congruence in the results of contemporary studies in observing that jobs with high demand, but high control, are a protective factor against suicidal ideation. This has been detected in Europe with work carried out in the Swedish context ( Almroth et al, 2022 ), and the conclusion gains cross-cultural validity as the phenomenon has also been observed in Japan ( Nishimura et al, 2022 ). The literature concludes that jobs with low control have a higher risk of suicide, which is accentuated by high demand.…”
Section: Work and Suicide Evidence: A Psychosocial Modelsupporting
confidence: 58%
See 2 more Smart Citations
“…The JDC model shows a congruence in the results of contemporary studies in observing that jobs with high demand, but high control, are a protective factor against suicidal ideation. This has been detected in Europe with work carried out in the Swedish context ( Almroth et al, 2022 ), and the conclusion gains cross-cultural validity as the phenomenon has also been observed in Japan ( Nishimura et al, 2022 ). The literature concludes that jobs with low control have a higher risk of suicide, which is accentuated by high demand.…”
Section: Work and Suicide Evidence: A Psychosocial Modelsupporting
confidence: 58%
“…This directly links the knowledge that social psychology is currently generating with the idea of disjunction in Abrutyn’s (2019) model. Thus, constructs related to work-related stress models and linked to suicide such as burn-out, observed in veterinarians, have been frequently examined ( Andela, 2021 ); the aforementioned job insecurity linked to suicidal ideation ( Kim et al, 2017 ; Blomqvist et al, 2022 ), and especially to the Job Demand-Control Model (JDC) ( Andela, 2021 ; Son and Lee, 2021 ; Aberg et al, 2022 ; Almroth et al, 2022 ; Nishimura et al, 2022 ). The JDC model shows a congruence in the results of contemporary studies in observing that jobs with high demand, but high control, are a protective factor against suicidal ideation.…”
Section: Work and Suicide Evidence: A Psychosocial Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…These kinds of mental symptoms can also lead to more serious consequences, such as suicide. A hierarchical cluster analysis from 2015 to 2016 showed that more than half of patients committed suicide within a month of developing a mental disorder, and the reason for this phenomenon was closely related to work patterns with overworking ( Nishimura, Yamauchi, Sasaki, Yoshikawa, & Takahashi, 2021 ). Moreover, employees with depressive symptoms are prone to low energy, sleep disorders, inattention at work and other problems, which can reduce work efficiency and performance ( Dewa, Hoch, Nieuwenhuijsen, Parikh, & Sluiter, 2019 ; Stewart, Ricci, Chee, Hahn, & Morganstein, 2003 ).…”
Section: Introductionmentioning
confidence: 99%
“…In Japan, more than half of the individuals commit suicide within a month of developing a mental disorder, and the suicide rate is higher among administrative and professional or engineering workers. Interpersonal conflict within the workplace serves as the primary catalyst for work-related suicides among individuals who are confronted with issues of chronic overwork and long working hours ( Nishimura et al, 2022 ). An analysis of suicides in South Korea showed a prominent cluster characterized by managers with excessive responsibility, termed as responsibility-burdened type of suicide ( Jang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%